AWARENESS OF HYPERTENSION AND ITS RISK FACTORS IN MAIDUGURI, NORTH EASTERN NIGERIA - Ibrahim Ummate; Ibrahim M. Kida; Abdullahi Talle; Bukar Bakki; Baba Waru Goni (Ntec Specialist, 2012)
Objectives: To determine the level of awareness of hypertension and its risk factors in Gwange community of Maiduguri North-eastern Nigeria. Method: A community based cross sectional study in Gwange community of Maiduguri, a major city in North-eastern Nigeria. Participants were selected through a stratified random sample method. Demographic data including age, gender, marital status, highest educational qualification and occupation were recorded. Information on awareness of hypertension and level of awareness of risk factors for hypertension were also obtained. Blood pressure was taken once on the left arm using a standard mercury sphygmomanometer. Results: In all, 485(175 females) were included. The study showed a statistically significant higher level of awareness among young individuals with declining trend with age (p=0.01). The study also recorded a statistically significant difference in the level of awareness of hypertension among individuals with different educational levels attained, with secondary and tertiary levels of education having higher awareness (p=0.00) and also a statistically significant difference in the awareness of hypertension among different occupational groups, with higher awareness among artisans and professionals (p=0.00). The study found 13 (6.5%) hypertensives among 199 individuals who are not aware of the risk factors for hypertension, 38 (21.6%) hypertensives among 176 individuals who are aware of one risk factor for hypertension, 12 (23.5%) hypertensives among 51 individuals who are aware of two risk factors for hypertension, and 11 (26.8%) hypertensives among 41 individuals who are aware of three or more risk factors for hypertension. Conclusion: Awareness of hypertension among hypertensives is higher than in normotensives with statistically significant higher awareness of its risk factors. Awareness is also found to be higher among people of young age group, secondary and tertiary levels of education and also among artisans and professionals. Special attention should be given to those living in remote villages and those least aware or treated in view of the consequences of hypertension on multiple organs and regular blood pressure check should be recommended to all individuals at risk